2017
DOI: 10.1021/acs.jpclett.7b02128
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Flexible Perovskite Solar Cells on Ultrathin Glass: Implications of the TCO

Abstract: For halide perovskite solar cells (PSCs) to fulfill their vast potential for combining low-cost, high efficiency, and high throughput production they must be scaled using a truly transformative method, such as roll-to-roll processing. Bringing this reality closer to fruition, the present work demonstrates flexible perovskite solar cells with 18.1% power conversion efficiency on flexible Willow Glass substrates. We highlight the importance of the transparent conductive oxide (TCO) layers on device performance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 23 publications
2
92
0
Order By: Relevance
“…AZO: aluminum‐doped zinc oxide; ITO: tin‐doped indium oxide; IZO: indium zinc oxide. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Flexible Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…AZO: aluminum‐doped zinc oxide; ITO: tin‐doped indium oxide; IZO: indium zinc oxide. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Flexible Substratesmentioning
confidence: 99%
“…Impressive progress has also been made with other diverse flexible substrates, such as CNT fiber, ultrathin flexible glass, muscovite mica, and nanopaper, among which, FPSCs based on ultrathin flexible willow glass shows the highest PCE over 18% . The ultrathin willow glass possesses high‐temperature tolerance up to 500 °C, together with a low thermal expansion coefficient of 2.5 × 10 −6 K −1 , which holds merits of being a substrate for the high‐temperature fabrication of FPSCs.…”
Section: Flexible Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…e) Structure diagram of flexible PSCs with a configuration of willow glass/TCO/(SnO 2 ETL)/CsMAFA/Spiro‐OMeTAD/MoO x /Au (TCO refers to transparent conductive oxide, such as ITO, IZO, or AZO). Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Configurations Of Sno2‐based Pscsmentioning
confidence: 99%
“…Willow glass has been used as the substrate material of flexible PSCs by Tavakoli et al Dou et al used willow glass as the flexible substrate and SnO 2 nanoparticles reported in ref. as the ETL material . They used different TCOs as the anode electrode of flexible solar cells, as shown in Figure e.…”
Section: Configurations Of Sno2‐based Pscsmentioning
confidence: 99%